TSUNAMI ACEH IN RELATIONSHIPS TO TECTONIC SOUTH GLOBE FRAME WORKS - Agus Sutiono (Jurnal Ilmiah MTG, 2010)
Since in the past 5 years a number of investigators have suggested in tsunami Aceh which was occurred in 26 Dec 2004 that because of subduction movement in causing earthquake with epicenter in the vicinity of sameuleu island located. Several of national and international Geophysical and geological studies have been systematically carried out in the studies design identified. However, in only a few of the some questions appear to be answered even several earthquake studies have also been simulated.The questions remain to be considered into other alternative concepts grading toward to the really mechanism of this tsunami further questions such as :1. Before tsunami was happened, sea water level firstly draw downed over the entire beaches and covering over the entire the countries such as Aceh (Indonesia), Thailand, Burma and India. Where has this sea water gone ?2. Epicenter of earthquake was in Simeuleu Island positioned that was in the South of Aceh, otherwise . Why Thailand and Burma where were behind or crossover Sumatra Island also occurred tsunami Rather than Padang in nearby ?There has not been clear answer on the direction of water tsunami movement to reach beaches. In particular causing its came from earthquake in Semeuleu island position where was behind Sumatera island to reach Thailand, Burma and India beaches.On the other hand, the data recording to the earthquake epicenters showed multiple positions adjacent to the Indian ocean trench indicating a zoning of subduction movement. At this time there is still insufficient evidence to determine the direction of tsunami movement mechanism that came from and along this subduction zone.Recent exposures in the Google earth imaging shows textures of Andaman sea floor polygons mosaic include sharp contacts and diffuse contacts of each others structures in relationship among these polygons.The textures descriptions and distribution of fault zone patterns with the models used onto Andaman sea floor studies which were essentially based on Google earth imaging. Hence, there are 4 forces direction indentified have been measured in causing of extension regions Which developed pull apart rifting. The initial force direction is about 22 (NE) rotated clock wise toward directions 46 (NE), 51 (NE) and finally 59 (NE).Jurnal Ilmiah MTG, Vol. 3, No. 1, Januari 2010The use of rotation direction force model in the study area . analog to its use in concepts both into pull apart basins for oil field and mineral deposit within dilatational jog structures. Once understanding of South global tectonic in development history will be required to solve the problem.Thus, at list 4 Mid Oceanic Ridges have been identified in the Southern globe. As indicated by the above discussion it is important that this information is recorded for feedback onto tectonic relationships analysis between Andaman and south globe.